Pharmacognostic Study of Some Phytochemically Unexploited Floristic Trees of Hathwa, Gopalganj (Bihar) - Kumari, Sarika; Ahmad, Sarfaraz (International Journal of Life Science and Pharma Research, 2021)
Pharmacognosy of Indian plants has been a perk for studies and medicinal researches. Hathwa has been blessed with Flora with extraordinary nutritional and medicinal benefits. Plants of Moringa oleifera (Lam.), Holarrhena antidysenterica (Roth)Wall, Erythrina indica (Lam.) were found to be present at outskirts of Hathwa region of Gopalganj Bihar, They have been traditionally used in several disorders faced by human body but the stringent record and detailing is missing and this research was accomplished to relate their antimicrobial activities with their phytochemical entities. The plant extracts of bark was chosen because of its abundance presence and easy availability. The extracts were found positive for phenol, quinine, steroids, protein and amino acids The time-kill kinetics profile of extract of bark of H. antidysentrica (Roth) against the test organisms K. pneumoniae, P. aeruginosa and V. cholerae at the test concentrations of Moringa oleifera showed reduction in number of viable cells over the first 4, 8, and 12 hours P. aeruginosa, and V. cholerae, respectively, followed by a gradual rise up to the 10th?h and 14thh for K. pneumoniae when compared to the control (organisms without antimicrobial agent).The time-kill kinetics profile of extract against the test organisms; at test concentrations studied showed reduction in number of viable cells over the first 2, 6, and 24 hours K. pneumoniae, P. aeruginosa, and V. cholerae respectively, followed by a gradual rise up to the 24thh for P. aeruginosa and V. choleraeand 12thh for K. pneumonia when compared to the control. Therefore from our research it was concluded that Moringa oleifera (Lam.), Holarrhena antidysenterica (Roth)Wall, Erythrina indica (Lam.) plants present at the outskirts of Hathwa region possess antimicrobial properties with important nutritional values. The aim of our research was to target some crucially important plants of Hathwa Gopalganj Bihar to study their antimicrobial potential, and this research targeted to explore the Phytoconstituents of those used plants which made them potent for antimicrobial activity.